2020
DOI: 10.1021/acs.iecr.0c03690
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and Heterogeneous Catalytic Kinetics in the Production of Triethyl Citrate

Abstract: This work deals with the determination of kinetic models for the esterification of citric acid with ethanol for the synthesis of triethyl citrate. Methanesulfonic acid (MSA) and an ion-exchange resin Amberlyst 70 (A70) were used as catalysts. Experiments were carried out under batch operation at temperatures between 345 and 393 K and at different initial reactant concentrations and catalyst loadings. The evolution of concentrations along the reaction was tracked by liquid chromatography. The proposed model cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Despite the merits of heterogenous catalyst, when comparing between using homogenous and heterogenous catalysts to produce TBC and TEC, it does not always guarantee the highest yield. Kinetic studies found that at specified conditions the homogenous catalyst (methane sulfonic acid), showed a higher catalytic performance compared to the heterogenous one (Amberlyst 70) for TBC 57 and for TE 61 …”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…Despite the merits of heterogenous catalyst, when comparing between using homogenous and heterogenous catalysts to produce TBC and TEC, it does not always guarantee the highest yield. Kinetic studies found that at specified conditions the homogenous catalyst (methane sulfonic acid), showed a higher catalytic performance compared to the heterogenous one (Amberlyst 70) for TBC 57 and for TE 61 …”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…[39][40][41] Moreover, TBC is useful as a solvent in the manufacturing of inks and coatings. [42] Tributyl citrate is typically synthesized via esterification of citric acid with 1butanol (BuOH) in the presence of a catalyst commonly sulfuric acid, p-toluenesulfonic acid, [43,44] ion-exchange resin [45][46][47] and supported [48][49][50] or solid acids. [51] Once the reaction is complete, the TBC is typically purified by distillation to remove any remaining water and unreacted starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerides and free fatty acids (FFA) in vegetable oils or animal fats can be converted to fatty acid alkyls esters (FAAE) by reactions with alcohols or esters. When the alkyl groups are methyl, these mixtures of fatty acid methyl esters (FAME), the biodiesel, have received considerable attention as diesel fuel substitutes, mainly if obtained through glycerol-free routes and from cheaper raw materials, such as vegetable oils with a high content of FFA, that provide better economic conditions for industries and mitigate the environmental problems. In this regard, the simultaneous acid reaction systems of FAME production between a low-cost glyceride feedstock and alcohols or esters become a promising alternative. For this route, unlike two-stage biodiesel production (the acid-catalyzed FFA reaction followed by the alkali-catalyzed glycerides reaction), the fixed and operating costs are lower. , For high acidity feedstocks, the FAME production from FFA becomes essential to obtain high biodiesel yields .…”
Section: Introductionmentioning
confidence: 99%